1996
DOI: 10.1042/bst024525s
|View full text |Cite
|
Sign up to set email alerts
|

INDUCTION OF INDUCIBLE NO-SYNTHASE IS AN ESSENTIAL PART OF TNFα-INDUCED APOPTOSIS IN McF-7 CELLS

Abstract: The TNFa-induced cytotoxic signal is mediated by the intracellular 'death domain' of the 55kD-TNF-receptor. In various cell types the death signal has been demonstrated to be coupled with induction of the inducible NO-Synthase (iNOS). However, it is still widely unknown, whether iNOSinduction is essential for TNF-cytotoxicity, especially in cells derived from sold t u r n .NO-producbjon and iNOS expression in relation to TNFa-induced cytotoxicity were therefore investigated in the human breast cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In this study, binding of TNFα to TNFR1 induced the expression of iNOS. Inhibition of iNOS activity abolished the cytotoxicity of TNFα in MCF7 and other TNFα-susceptible cells (Binder et al, 1999). In a separate experiment, HeLa cells transfected with eNOS were found to be resistant to TNFα-mediated apoptosis.…”
Section: Receptorsmentioning
confidence: 89%
“…In this study, binding of TNFα to TNFR1 induced the expression of iNOS. Inhibition of iNOS activity abolished the cytotoxicity of TNFα in MCF7 and other TNFα-susceptible cells (Binder et al, 1999). In a separate experiment, HeLa cells transfected with eNOS were found to be resistant to TNFα-mediated apoptosis.…”
Section: Receptorsmentioning
confidence: 89%
“…It remains to be determined whether HER2/neu-induced suppression of NO in breast cancer is a mechanism specific to retinoids or whether it has a broader effect on chemotherapy and hormone resistance. This is particularly important, as NO production has been linked to apoptosis induction by chemotherapeutic and biological agents, including doxorubicin (Kalivendi et al, 2001) and tumor necrosis factor-a (Binder et al, 1999). Future studies will be conducted to determine the mechanisms involved in the HER2/neu-mediated suppression of 4-HPR-induced NOSII expression and NO production in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is involved in survival of TNF-α-treated cells through NF-κB-induced expression of inducible NO synthase (iNOS) [91,92]. We have previously shown that inhibition of NOS by the addition of L-NAME (NG-nitro-L-arginine methyl ester) during TNF-α-based ILP resulted in an increased tumor response in rats bearing STSs [93].…”
Section: Approaches To Modulate Tnf-α Action In Cancer Treatmentmentioning
confidence: 99%